Everyday chaos : technology, complexity, and how we're thriving in a new world of possibility - Weinberger, David, 1950- (Boston : Harvard business Review Press, 2019)
Modern science, the Internet, big data, and AI are each saying the same thing to us: the world is -- and always has been -- far more complex and unpredictable than we've allowed ourselves to see. As a result we're undergoing a sea change in our understanding of how things happen, and in our deepest strategies for predicting, preparing for, and managing our lives and our businesses. For example, machine learning allows us to make better predictions (think the weather, stock performance, online clicks) but we know less about why those predictions are right--and we need to get used to that. And in fact, over the past twenty years we've been unintentionally developing strategies that avoid anticipating what will happen so we don't have to depend on unreliable revenue forecasts, assumptions about customer needs, and hypotheses about how a product will be used. By embracing these strategies, we're flourishing by creating yet more possibilities and yet more unpredictability. In wide-ranging stories and characteristically all-encompassing syntheses, technology researcher, internet expert, and philosopher David Weinberger reveals the trends that hide in so many aspects of our lives--and shows us how they matter.--
Introduction: Everything all at once -- The evolution of prediction -- Inexplicable models -- Beyond preparation: unanticipation -- Beyond causality: interoperability -- Strategy and possibility -- Progress and creativity -- Make. more. meaning.
Includes bibliographical references and index.
Keywords: Chaotic behavior in systems -- Industrial applications; Complexity ; chaos; Economic forecasting; Prediction theory -- Technological innovations; Technological innovations